COVID-19 UNMASKED: INSIGHTS INTO ELECTROLYTE AND TRACE ELEMENT DISTURBANCES - Elhassan, Fatima Ahmed; Eltayeb , Omar Abdelrahman; Abdallah, Sara Ibrahim (Research Journal of Health, Medicine and Nursing, 2024)
Coronaviruses, named for their characteristic "halo" or "crown" appearance, belong to the family of enveloped, positive-sense single-stranded RNA viruses with a genome size ranging from 26 to 32 kbs. These zoonotic infections, originating in animals, can be transmitted directly from animals to humans and subsequently from person to person. The emergence of COVID-19, initially linked to a seafood market in Wuhan, China, prompted swift actions by Chinese authorities, including the closure of the implicated market. Infection primarily spreads through respiratory droplets, close personal contact, and less commonly through fecal-oral routes, necessitating quarantine measures for exposed individuals. Electrolytes, crucial compounds that dissolve in body fluids and conduct electrical currents, play a vital role in maintaining homeostasis. Both extracellular and intracellular fluids contain electrolytes, emphasizing their significance in regulatory processes. Hyponatremia, a disorder affecting electrolyte balance, manifests with neurological symptoms such as headaches, disorientation, confusion, and nausea. Conversely, hypernatremia, characterized by elevated serum sodium levels, presents with symptoms like tachypnea, insomnia, and agitation. The entry of the coronavirus into the host's system has noteworthy effects on the renin-angiotensin-aldosterone system. The virus reduces the expression of ACE2, preventing the degradation of angiotensin II. This, in turn, leads to an upsurge in aldosterone production, resulting in potassium loss through urine. Understanding these intricate interactions between the virus and the host's regulatory systems is crucial for comprehending the diverse clinical manifestations associated with COVID-19. This abstract highlights the multifaceted nature of coronaviruses, emphasizing their zoonotic origins, modes of transmission, and the impact on electrolyte balance within the human body. Furthermore, it underscores the importance of recognizing and managing electrolyte disorders, such as hyponatremia and hypernatremia, in COVID-19 patients. As the scientific community continues to unravel the complexities of coronavirus infections, this synthesis of virological and physiological aspects contributes to a more comprehensive understanding of the ongoing global health challenge.